A Rare Case of Cutaneous Plasmacytosis in a Korean Male - Corey Georgesen; Meenal Kheterpal; Melissa Pulitzer (Case Reports in Pathology)
Cutaneous and systemic plasmacytosis are reactive disease processes that occur in middle-aged Japanese and Chinese men. Systemic plasmacytosis, defined by plasmacytic infiltration of two organ systems, might rarely progress to lymphoma. Cutaneous plasmacytosis, however, is chronic and benign and is characterized by the development of multiple plasma cell-rich infiltrates in the skin. We present a case of cutaneous plasmacytosis in a 46-year-old Korean male. The patient demonstrated classic features of the disease entity, including disseminated red-brown plaques, differentiated plasmacytoid infiltrates on biopsy, hypergammaglobulinemia, and the absence of systemic disease.